3D printing for rapid sand casting—A review. (October 2017) - Upadhyay, Meet; Sivarupan, Tharmalingam; El Mansori, Mohamed
Abstract: There are many 3D printing technologies available, and each technology has its strength and weakness. The 3D printing of sand moulds, by binder jetting technology for rapid casting, plays a vital role in providing a better value for the more than 5000 years old casting industry by producing quality and economic sand moulds. The parts of the mould assembly can be manufactured by precisely controlling the process parameters and the gas producible materials within the printed mould. A functional mould can be manufactured with the required gas permeability, strength, and heat absorption characteristics, and hence the process ensures a high success rate of quality castings with an optimised design for weight reduction. It overcomes many of the limitations in traditional mould design with a very limited number of parts in the mould assembly. A variety of powders, of different particle size or shape, and bonding materials can be used to change the thermal and physical properties of the mould and hence provide possibilities for casting a broad range of alloys. Limited studies have been carried out to understand the relationship between the characteristics of the printed mould, the materials used, and the processing parameters for making the mould. These deficiencies need to be addressed to support the numerical simulation of a designed part, to optimise the success rate and for economic as well as environmental reasons. Commonly used binders in this process, e.g. furan resins, are carcinogenic or hazardous, and hence there is a vital need for developing new or improved bonding materials.